Sikap dan Pola Asuh Orang Tua terhadap Perkembangan Anak Usia Toddler - Eny Pemilu Kusparlina; Muwakhidah Muwakhidah; Mufida Dian Hardika; Eddy Wasito (FORIKES, 2024)
Parents are the first personal guidance in a child's life. The personality, attitudes and way of life of parents are indirect elements of education, which will naturally enter into the personality of the growing child. Sometimes parents forget their obligation to monitor their child's development because they are busy with their own work. Materials are often the reason why parents often work and leave their children at home. The aim of this research was to analyze the influence of parenting patterns and parental attitudes on the development of toddler-aged children. This research implemented a cross-sectional design, which was conducted in Manisrejo Village, Taman District, Madiun City. This study involved 60 parents with toddler-aged children, who were selected using a simple random sampling technique. Data about parenting patterns, attitudes and development of toddler-aged children was taken through filling out questionnaires. Data were analyzed using Chi-square test. The results of the analysis show that the p value for each factor is parenting style = 0.000 and parental attitude = 0.000. Furthermore, it was concluded that parenting patterns and parental attitudes influence the development of toddler-aged children.Keywords: toddler; development; attitude; parenting ABSTRAK Orang tua adalah pembinaan pribadi yang pertama dalam kehidupan anak. Kepribadian, sikap dan cara hidup orang tua merupakan unsur-unsur pendidikan yang tidak langsung, yang dengan sendirinya akan masuk ke dalam pribadi anak yang sedang tumbuh. Terkadang orang tua lupa akan kewajibannya dalam mengawasi perkembangan anak karena sibuk dengan pekerjaannya sendiri. Materi sering menjadi alasan betapa seringnya orang tua bekerja dan meninggalkan anaknya di rumah. Tujuan penelitian ini adalah untuk menganalisis pengaruh pola asuh dan sikap orang tua terhadap perkembangan anak usia toddler. Penelitian ini menerapkan rancangan cross-sectional, yang dilakukan di Desa Manisrejo, Kecamatan Taman, Kota Madiun. Studi ini melibatkan 60 orang tua yang mempunyai anak usia toddler, yang dipilih dengan teknik simple random sampling. Data tentang pola asuh, sikap dan perkembangan anak usia toddler diambil melalui pengisian kuesioner. Data dianalisis dengan uji Chi-square. Hasil analisis menunjukkan nilai p untuk masing-masing faktor adalah pola asuh orang tua = 0,000 dan sikap orang tua = 0,000. Selanjutnya disimpulkan bahwa pola asuh dan sikap orang tua berpengaruh terhadap perkembangan anak usia toddler.Kata kunci: toddler; perkembangan; sikap; pola asuh